2020
DOI: 10.1097/md.0000000000022046
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacies of unipedicular kyphoplasty and bipedicular kyphoplasty for treatment of single-level osteoporotic vertebral compression fractures

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In 2010, Chen et al 13 reported that bipedicular PKP was more effective than unipedicular PKP in improving vertebral height. More recently, in their 2020 study, Lee et al 9 reported no differences in height restoration between the two techniques. We also concluded that both techniques provided similar restoration of vertebral height, with no differences in anterior or middle vertebral heights post-operatively.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In 2010, Chen et al 13 reported that bipedicular PKP was more effective than unipedicular PKP in improving vertebral height. More recently, in their 2020 study, Lee et al 9 reported no differences in height restoration between the two techniques. We also concluded that both techniques provided similar restoration of vertebral height, with no differences in anterior or middle vertebral heights post-operatively.…”
Section: Discussionmentioning
confidence: 92%
“…Zhang et al 14 reported bone cement leakage rates of 20.8% (5 of 24) in the unipedicular group and 34.6% (9 in 26) in the bipedicular group, which did not differ signi cantly between groups. Lee et al 9 reported no signi cant difference in the leakage rates of cement into the intradiscal space (14% in the unipedicular group and 18% in the bipedicular group). A 2019 meta-analysis by Chen et al concluded that the unilateral approach decreased the incidence of cement leakage in PKP 26 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Also, Lin et al (12) reported that despite the advantages of unilateral puncture, the risk of arteriovenous injury and cement leakage during puncture is significantly increased by increasing the volume of cement injection in order to distribute cement evenly within the vertebral body. In a recent retrospective study, Lee et al (13) pointed out that as a level 3 evidence and grade B recommendation, unipedicular kyphoplasty requires lower amounts of cement than bipedicular kyphoplasty and is as effective as bipedicular kyphoplasty in terms of radiological and clinical outcomes. Furthermore, Cui et al (14) reported that unilateral PKP is superior to bilateral PKP in shortening operation time and bone cement leakage.…”
Section: Advantages and Disadvantages Of Unilateral And Bilateral Pkpmentioning
confidence: 99%
“…In recent years, unipedicular approach has been advocated because of shorter operating and radiation exposure times, which can lower the risk of cement leakage and complications. Most previous studies have shown that the clinical and radiological results of unipedicular percutaneous kyphoplasty for OVCFs are similar to those of bipedicular percutaneous kyphoplasty [ 7 9 ]. However, the previous studies have mostly focused on the thoracolumbar spine, and there are few reports on the lower lumbar spine (L3–L5).…”
Section: Introductionmentioning
confidence: 96%